Molecular Testing and Treatment Strategies in RET-Rearranged NSCLC Patients: Stay on Target to Look Forward - Maria Lucia Reale; Valentina Bertaglia; Angela Listì; Silvia Novello; Francesco Passiglia (MDPI AG, 2022)
RET alterations are recognized as key oncogenic drivers in different cancer types, including non-small cell lung cancer (NSCLC). Multikinase inhibitors (MKIs) with anti-RET activities resulted in variable efficacy with significant toxicities because of low target specificity. Selective RET kinase inhibitors, such as pralsetinib and selepercatinib, demonstrated high efficacy and favorable tolerability in advanced RET-rearranged NSCLC patients, leading to their introduction in the clinical setting. Among the different approaches available for the identification of RET rearrangements, next-generation sequencing (NGS) assays present substantial advantages in terms of turnaround time and diagnostic accuracy, even if potentially limited by accessibility issues. The recent advent of novel effective targeted therapies raises several questions regarding the emergence of resistance mechanisms and the potential ways to prevent/overcome them. In this review, we discuss molecular testing and treatment strategies to manage RET fusion positive NSCLC patients with a focus on resistance mechanisms and future perspectives in this rapidly evolving scenario.